2004
DOI: 10.1038/sj.bjc.6602024
|View full text |Cite
|
Sign up to set email alerts
|

An antagonist of retinoic acid receptors more effectively inhibits growth of human prostate cancer cells than normal prostate epithelium

Abstract: Screening of synthetic retinoids for activity against prostate carcinoma cell lines has identified antagonists of retinoic acid receptors (RARs) as potent growth inhibitors (Hammond et al, 2001, Br J Cancer 85, 453 -462). Here we report that 5 days of exposure to a high-affinity pan-RAR antagonist (AGN194310) abolished growth of prostate carcinoma cells from 14 out of 14 patients, with halfmaximal inhibition between 200 and 800 nM. It had similar effects (at B250 nM) on the prostate carcinoma lines LNCaP, DU-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 46 publications
5
28
0
Order By: Relevance
“…Activation of RARγ favors cell proliferation and survival as opposed to differentiation [40]. As such, RARγ antagonists interfere with cell growth [41]. Here, RARα agonist AM580 or RARγ antagonist SR11253 had similar reductions in cell viability (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Activation of RARγ favors cell proliferation and survival as opposed to differentiation [40]. As such, RARγ antagonists interfere with cell growth [41]. Here, RARα agonist AM580 or RARγ antagonist SR11253 had similar reductions in cell viability (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a RAR-a-specific antagonist LG100629 was shown to block essentially completely the induction of IGFBP3 and TGFB2 by RA in human bronchial epithelial cells (26), in contrast to our findings with pan-RAR modulator LG100815. On the other hand, several RAR antagonists, similarly to LG100815, were found to inhibit tumor cell growth (27)(28)(29)(30). It would be of interest to determine if these compounds act as LG100815-type RAR modulators.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that the mechanism(s) of action of these synthetic retinoid-related molecules does not appear to involve retinoid receptors. Keedwell et al [74] showed that a retinoid-related molecule, which neither binds effectively to RARs and RXRs nor transactivates in RAR-and RXRmediated reporter assays, rapidly induced apoptosis in primary cultures from PCa, thus opening a new field of studies about non-classical actions of retinoids. On the other hand, studies showed that synthetic retinoids antagonizing RARs are potent growth inhibitors of PCa cell lines [45].…”
Section: Retinoids and Prostate Cancermentioning
confidence: 98%
“…On the other hand, studies showed that synthetic retinoids antagonizing RARs are potent growth inhibitors of PCa cell lines [45]. Keedwell et al [74] showed that 5 days of exposure to a high-affinity pan-RAR antagonist (AGN194310) abolished growth of PCa cells from 14 out of 14 patients, with half-maximal inhibition between 200 and 800 nM; it had similar effects (at approximately 250 nM) on the PCa lines LNCaP, DU-145, and PC-3. AGN194310 inhibited the growth of normal prostate epithelium cells less potently, by 50% at approximately 1 uM.…”
Section: Retinoids and Prostate Cancermentioning
confidence: 99%